Maternal protein restriction during lactation modulated the expression and activity of rat offspring hepatic CYP1A1, CYP1A2, CYP2B1, CYP2B2, and CYP2E1 during development - Da Costa,N. Meireles (2016)
Early nutrition plays a long-term role in the predisposition to chronic diseases and influences the metabolism of several drugs. This may happen through cytochromes P450 (CYPs) regulation, which are the main enzymes responsible for the metabolism of xenobiotics. Here, we analyzed the effects of maternal protein restriction (MPR) on the expression and activity of hepatic offspring’s CYPs during 90 days after birth, using Wistar rats as a mammal model. Hepatic CYP1A1, CYP1A2, CYP2B1, CYP2B2 and CYP2E1 mRNA and protein expression, and associated catalytic activities (ECOD, EROD, MROD, BROD, PROD and PNPH) were evaluated in 15-, 30-, 60-, and 90-day-old offspring from dams fed with either a 0% protein (MPR groups) or a standard diet (C groups) during the 10 first days of lactation. Results showed that most CYP genes were induced in 60- and 90-day-old MPR offspring. The inductions detected in MPR60 and MPR90 were of 5.0- and 2.0-fold (CYP1A2), 3.7- and 2.0-fold (CYP2B2) and 9.8- and 5.8– fold (CYP2E1), respectively, and a 3.8-fold increase of CYP2B1 in MPR90. No major alterations were detected in CYP protein expression. The most relevant CYP catalytic activities’ alterations were observed in EROD, BROD and PNPH. Nevertheless, they did not follow the same pattern observed for mRNA expression, except for an induction of EROD in MPR90 (3.5-fold) and of PNPH in MPR60 (2.2-fold). Together, these results suggest that MPR during lactation was capable of altering the expression and activity of the hepatic CYP enzymes evaluated in the offspring along development.